Gga-miR-19b-3p Inhibits Newcastle Disease Virus Replication by Suppressing Inflammatory Response via Targeting RNF11 and ZMYND11 - Chen, Yu; Liu, Wen; Xu, Haixu; Liu, Jingjing; Deng, Yonghuan; Cheng, Hao; Zhan, Tiansong; Lu, Xiaolong; Liao, Tianxing; Guo, Lili; Zhu, Shanshan; Pei, Yuru; et al. (Frontiers in Microbiology, 2019)
Newcastle disease (ND), an acute and highly contagious avian disease caused by virulent Newcastle disease virus (NDV), often results in severe economic losses worldwide every year. Although it is clear that microRNAs (miRNAs) are implicated in modulating innate immune response to invading microbial pathogens, their role in host defense against NDV infection remains largely unknown. Our prior study indicates that gga-miR-19b-3p is up-regulated in NDV-infected DF-1 cells (a chicken embryo fibroblast cell line) and functions to suppress NDV replication. Here we report that overexpression of gga-miR-19b-3p promoted the production of NDV-induced inflammatory cytokines and suppressed NDV replication, whereas inhibition of endogenous gga-miR-19b-3p expression had an opposite effect. Dual-luciferase and gene expression array analyses revealed that gga-miR-19b-3p directly targets the mRNAs of ring finger protein 11 (RNF11) and zinc-finger protein, MYND-type containing 11 (ZMYND11), two negative regulators of nuclear factor kappa B (NF-κB) signaling, in DF-1 cells. RNF11 and ZMYND11 silencing by small interfering RNA (siRNA) induced NF-κB activity and inflammatory cytokine production, and suppressed NDV replication; whereas ectopic expression of these two proteins exhibited an opposite effect. Our study provides evidence that gga-miR-19b-3p activates NF-κB signaling by targeting RNF11 and ZMYND11, and that enhanced inflammatory cytokine production is likely responsible for the suppression of NDV replication.